Electrochemically Driven Water Oxidation by a Highly Active Ruthenium‐Based Catalyst. Issue 10 (12th April 2019) - Shatskiy, Andrey; Bardin, Andrey A.; Oschmann, Michael; Matheu, Roc; Benet‐Buchholz, Jordi; Eriksson, Lars; Kärkäs, Markus D.; Johnston, Eric V.; Gimbert‐Suriñach, Carolina; Llobet, Antoni; Åkermark, Björn
Abstract: The highly active ruthenium‐based water oxidation catalyst [Ru X (mcbp)(OH n )(py)2 ] [mcbp 2− =2, 6‐bis(1‐methyl‐4‐(carboxylate)benzimidazol‐2‐yl)pyridine; n =2, 1, and 0 for X=II, III, and IV, respectively], can be generated in a mixture of Ru III and Ru IV states from either [Ru II (mcbp)(py)2 ] or [Ru III (Hmcbp)(py)2 ] 2+ precursors. The precursor complexes are isolated and characterized by single‐crystal X‐ray analysis, NMR, UV/Vis, EPR, and FTIR spectroscopy, ESI‐HRMS, and elemental analysis, and their redox properties are studied in detail by electrochemical and spectroscopic methods. Unlike the parent catalyst [Ru(tda) (py)2 ] (tda 2− =[2, 2′:6′, 2′′‐terpyridine]‐6, 6′′‐dicarboxylate), for which full transformation into the catalytically active species [Ru IV (tda)(O)(py)2 ] could not be carried out, stoichiometric generation of the catalytically active Ru–aqua complex [Ru X (mcbp)(OH n )(py)2 ] from the Ru II precursor was achieved under mild conditions (pH 7.0) and short reaction times. The redox properties of the catalyst were studied and its activity for electrocatalytic water oxidation was evaluated, reaching a maximum turnover frequency (TOFmax ) of around 40 000 s −1 at pH 9.0 (from foot‐of‐the‐wave analysis), which is comparable to the activity of the state‐of‐the‐art catalyst [Ru IV (tda)(O)(py)2 ]. Abstract : Ru ready? A highly active catalyst, [Ru X (mcbp)(OH n )(py)2 ] [mcbp 2− =2, 6‐bis(1‐methyl‐4‐(carboxylate)benzimidazol‐2‐yl)pyridine], is described and applied in electrocatalytic water oxidation. Stoichiometric generation of the catalytically active Ru–aqua complex is achieved quickly under mild conditions, which allows its electrocatalytic activity to be evaluated.